Tactical efficacy and offensive game processes adopted by Italian and Brazilian youth soccer players - Paulo Henrique Borges; Júlio Garganta; José Guilherme; Matheus de Oliveira Jaime; Vanessa Menezes Menegassi; Leandro Rechenchosky; Dourivaldo Teixeira; Wilson Rinaldi
Abstract Aim: To analyze success and failure of offensive sequences and the adopted offensive method in under-15 (U-15) and under-17 (U-17) soccer players. Methods: The sample was composed of 218 offensive sequences performed by U-15 and U-17 players selected from 28 matches, being 18 matches of an Italian team and 10 matches of a Brazilian team. All offensive sequences which ended in finalization were selected for the analysis. Using observational methodology, an adapted ad hoc observational instrument was built with the variables "number of players involved", "ball touches", "passing", "duration", and "corridor changes". Next, offensive actions were classified into three offensive game methods: counter-attack, quick attack, and positional attack. Results: Results revealed that teams which use positional attack expend more time constructing an offensive play, involve extra players, and change the ball corridor more often during offensive actions when compared to counter-attack and quick attack (p<0.01). Moreover, offensive efficacy did not present an association with the offensive method employed (X2=0.47; p=0.78). Sequences that finished in success presented significantly higher values of the number of touches (p=0.02), passes (p=0.003), and duration (p=0.01) in comparison to failure. Conclusion: The findings suggest that all offensive methods adopted can be used to reach success during a game of U-15 and U-17 soccer players.